Comparison of Heart Rate Response to an Epinephrine Test Dose and Painful Stimulus in Children During Sevoflurane Anesthesia: Heart Rate Variability and Beat-to-Beat Analysis. Issue 5 (1st September 2003) - Wodey, Eric; Senhadji, Lotfi; Bansard, Jean Yves; Terrier, Anne; Carré, François; Ecoffey, Claude
Abstract : Background and objectives: During regional anesthesia, various stimuli leading to an adrenergic response can occur. However, simulation of an epidural test dose by using intravenous administration of epinephrine (EPI) has always been compared with an intravenous saline infusion as the control. The aim of this study was to evaluate the possibility of distinguishing in children the effect on HR by an intravascular epinephrine infusion and a painful stimulus, using heart rate variability (HRV) and beat-to-beat analysis of HR. Methods: Thirty American Society of Anesthesiologists physical status P I children who required elective surgery were studied. At 1 minimum alveolar concentration (MAC) of sevoflurane, electrocardiogram was recorded continuously. Systolic blood pressure (SBP) was measured every minute. Measurements were performed after an intravenous administration of 0.5 μg/kg of epinephrine and during a small skin surgical incision (SI). Time-varying auto-regressive modeling of the interpolated RR sequences was performed for estimating power spectrum (msec 2 ). The HF bands were defined by (0.15-0.4 Hz). Results: Median (range) age and weight of all children were 3.5 (1-10) years and 16 (9-30) kg. EPI produced a lower increase in HR than did SI. SBP increased significantly more than did after SI. T-wave amplitude increased significantly after EPI but not after SI. Sixty seconds after the first change in HR, a secondary decrease (in comparison to control value) can be detected with EPI in contrast to SI. HF spectral power increased significantly after EPI administration but decreased after SI. The sensitivity, specificity, and positive and negative predictive value were respectively for ΔHR >10 beats per minuteof 56%, 26%, 43%, and 38%; for ΔSBP >15 mm Hg of 60%, 86%, 81%, and 67%; and for ΔT-wave amplitude >25% of 86%, 73%, 76%, and 84%. Using detection of the secondary decrease of HR, 60 seconds after the first change in HR, sensitivity, specificity, and positive and a negative predictive value were respectively 96%, 100%, 100%, and 96%. Conclusions: Detection of the secondary HR decrease, 60 seconds after the first change in HR, allows us to distinguish the effects of a painful stimulus from those related to the epinephrine test dose at 1 MAC of sevoflurane. This secondary HR decrease induced by epinephrine appears primarily because of a compensatory increase in parasympathetic tone.